2018
DOI: 10.1002/chem.201800086
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Pincer Ligand for Cobalt‐Promoted Oxidation by N2O

Abstract: The divalent cobalt complex of the diprotic pincer ligand bis-pyrazolylpyridine, (H L)CoCl , is dehydrohalogenated twice by LiN(SiMe ) in the presence of PEt to give monomeric S=1/2 LCo(PEt ) (1), fully characterized in the solid-state and solution as a square pyramidal monomer with a long axial Co-P bond. This 17-electron species reacts in time of mixing with N O to form L Co (μ-OPEt ) (2)+3 OPEt , the former the first example of phosphine oxide bridging two transition metals. The same products are formed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…However, this situation differs due to the ions’ high Lewis acidity from the cases of the larger monovalent ions, in that, (i) multiple TPPO molecules can likely bind to each acidic divalent metal ion (for example, at small ion/TPPO ratios) and (ii) multiple divalent metals could bind to a single TPPO unit (for example, at large ion/TPPO ratios). In line with this theory, the few relevant results available from single-crystal X-ray diffraction (XRD) studies reported in the Cambridge Structural Database reveal that phosphine oxides can serve as bridging ligands between redox-inactive metal ions like Na + and Co 2+ . , Thus, it is reasonable to imagine that the positive cooperativity measured for the divalent ions is associated with, in part, the formation of multimetallic complexes bridged by TPPO ligands. The formation of such structures could presumably help satisfy the demanding coordination requirements of the voraciously Lewis acidic divalent ions.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this situation differs due to the ions’ high Lewis acidity from the cases of the larger monovalent ions, in that, (i) multiple TPPO molecules can likely bind to each acidic divalent metal ion (for example, at small ion/TPPO ratios) and (ii) multiple divalent metals could bind to a single TPPO unit (for example, at large ion/TPPO ratios). In line with this theory, the few relevant results available from single-crystal X-ray diffraction (XRD) studies reported in the Cambridge Structural Database reveal that phosphine oxides can serve as bridging ligands between redox-inactive metal ions like Na + and Co 2+ . , Thus, it is reasonable to imagine that the positive cooperativity measured for the divalent ions is associated with, in part, the formation of multimetallic complexes bridged by TPPO ligands. The formation of such structures could presumably help satisfy the demanding coordination requirements of the voraciously Lewis acidic divalent ions.…”
Section: Resultsmentioning
confidence: 96%
“…In line with this theory, the few relevant results available from single-crystal X-ray diffraction (XRD) studies reported in the Cambridge Structural Database 41 reveal that phosphine oxides can serve as bridging ligands between redoxinactive metal ions like Na + and Co 2+ . 35,42 Thus, it is reasonable to imagine that the positive cooperativity measured for the divalent ions is associated with, in part, the formation of multimetallic complexes bridged by TPPO ligands. The formation of such structures could presumably help satisfy the demanding coordination requirements of the voraciously Lewis acidic divalent ions.…”
Section: Resultsmentioning
confidence: 99%
“…Considering this finding for binding of divalent metal ions to TPPO, we first mention that the few relevant results available from single-crystal X-ray diffraction (XRD) studies in the Cambridge Structural Database 39 reveal that phosphine oxides can serve as bridging ligands between redox-inactive metal ions like Na + and Co 2+ . 33,40 Thus, it is reasonable to imagine that multiple divalent metals could bind to a single TPPO unit. We anticipate that the positive cooperativity measured here is associated with formation of metal complexes bridged by TPPO ligands; for example, formation of a single μ2-TPPO bridge could promote binding of a second bridging μ2-TPPO.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their potential applications in the field of homogeneous catalysis, there is a significant research interest in multifunctional ligands based on pyrazole [1–5] . Moreover, polydentate pyrazole‐based ligands have gained relevance as potential metalloprotein mimetics, [6–8] and as building blocks for metal‐organic frameworks [9–13] .…”
Section: Introductionmentioning
confidence: 99%